Association between Board of Director Characteristics and the Amount of Voluntary Audit Committee Disclosures - Van der Zahn, Jean-Luc Wolfgang Mitchell (Institutional Knowledge at Singapore Management University, 2004)
This study empirically examines the association between certain director characteristics and the extent of voluntary audit committee disclosure in annual reports. Results suggest that Singapore's publicly traded firms are more likely to voluntarily disclose audit committee related information as: the number of board members increases; different individuals occupy the roles of CEO and board chairperson; and the proportion of independent directors serving on the board increases. Findings, however, fail to show any association between the amount of voluntary audit committee disclosure and the percentage of executive directors' ownership. Documented findings are of interest and benefit to various parties including regulators, corporate governance reformists, and corporate management. For instance, findings imply that a positive by-product of implementing major corporate governance reforms currently championed by corporate governance reformists will be an increase in audit committee disclosures. As a result, there will be less pressure on regulators to develop, introduce, and enforce mandatory audit committee disclosures that may be potentially intrusive to a firm's management.